Moving beyond 30 years of Anglo-American rape law reforms: Legal representation for victims of sexual offences - Smythe, Dee (2016)
The South African Law Commission has proposed a number of substantive and procedural reforms to South Africa's laws governing sexual offences. This article argues that, while important in principle, these reforms are unlikely to shift police and prosecution practices or to meaningfully increase the numbers of offences prosecuted or perpetrators convicted. Support for this argument is drawn from the experiences of other Anglo-American jurisdictions in implementing similar reforms. The current law reform process does, however, present an important opportunity to consider possible reforms that have the potential to shift institutional norms informing current criminal justice practice, and to provide meaningful protection for victims of sexual offences forced to navigate that system. One such reform, which has met with some success in other jurisdictions, is the introduction of a legal representative to engage with the criminal justice process on behalf of the victim. This article looks at the legal and constitutional rationale for such an innovation and at models used in comparative jurisdictions, concluding that such a reform would go a long way towards ensuring that the existing rights of rape victims are meaningfully enforced